2020
DOI: 10.2174/1385272824999200922090524
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Appraisal of Chalcones and Their Heterocyclic Analogs as Antimicrobial Agents

Abstract: : Owing to the growing demand of compelling antimicrobial agents, chalcones and their heterocyclic derivatives have engrossed prodigious attention of medicinal chemists as effective clinical template for the synthesis of such agents on account of their structural diversity and molecular flexibility. Chalcones are celebrated as fortunate scaffold in an area of both synthetic as well as natural product chemistry. They are reflected as remarkable section of logically occurring pharmacophore that possess comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 112 publications
0
1
0
Order By: Relevance
“…Heteroaryl chalcones are obtained by modifications of phenyl rings [21,22]. Several studies have shown that heteroaryl chalcones have widespread biological potential such as anti-fungal, antibacterial, antimalarial, anticancer, anti-inflammatory, anti-angiogenic and anti-HIV activities [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Heteroaryl chalcones are obtained by modifications of phenyl rings [21,22]. Several studies have shown that heteroaryl chalcones have widespread biological potential such as anti-fungal, antibacterial, antimalarial, anticancer, anti-inflammatory, anti-angiogenic and anti-HIV activities [23,24].…”
Section: Introductionmentioning
confidence: 99%